Magnetic Resonance Imaging-Guided Treatment of Equine Distal Interphalangeal Joint Collateral Ligaments: 2009–2014 - White, Nathaniel A.; Barrett, Jennifer G. (Frontiers in Veterinary Science, 2016)
Objectives: To determine the success of treating distal interphalangeal joint collateral ligament (DIJCL) desmopathy using magnetic resonance imaging (MRI) guided ligament injection. Methods: Medical records of 13 adult horses diagnosed with DIJCL desmopathy using low field MRI and treated by MRI guided ligament injection of mesenchymal stem cells and/or platelet rich plasma were reviewed. Information collected included signalment, MRI diagnosis, treatment type, time to resolution of lameness and level of exercise after treatment. Results: Collateral ligament inflammation was diagnosed as a cause of lameness in 13 horses. MRI was used to guide the injection of the injured DIJCL. All lameness attributed to DIJCL desmopathy resolved with the resulting level of performance at expected (10) or less than expected (3). Conclusions and Clinical Relevance: Injection of the DIJCL can be completed in horses standing in a low field magnet guided by MRI as previously demonstrated in cadaver specimens. Administration of stem cells or PRP appears useful as a treatment for DIJCL desmopathy.